THE ROLE OF LOCAL GOVERNMENT BODIES IN ENTREPRENEURSHIP DEVELOPMENT (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the role of local government bodies in entrepreneurship development based on empirical analysis of 14 regions in Uzbekistan covering 2020-2024.